Painting by numbers: A GMT primer for merging swath-mapping sonar data of different types and resolutions - Becker, Nathan C. (Computers & geosciences, 2005)
Swath-mapping sonar systems are used to map the sea floor either by collecting bathymetry or backscatter data. However, the manipulation of such data to produce maps for interpretation requires specialized expertise that most geologists do not possess. This paper is intended to introduce a geoscientist to the Generic Mapping Tools and to supplement existing documentation for this software package by showing how to use it to process data gathered from swath-mapping sonar systems. Though this document is intended to be an introductory text and includes some basic examples, it will also introduce the novice user to more sophisticated techniques for merging data sets from a variety of sources and types, and will conclude with an algorithm for merging bathymetry with backscatter imagery.